(untitled) (MAUSAM, 1977)
A radar study of heights of tops of Cumulonimbus clouds over the Deccan Plateau and adjoining plains of Andhra Pradesh and east Maharashtra is presented in this paper. The study is based on all routine and non-routine weather radar observations taken and recorded by the meteorological office, Hyderabad Airport (Andhra Pradesh) during a five-year period from June 1969 to May 1974. Frequency distribution at different height intervals and also for different periods of the day have been computed. A season wise analysis has also been made.